Evidence-Based Nursing Education - Zabidah, Putit (2013)
Nursing is accountable to the community and society, not only in delivering nursing care but providing quality, cost-effective care and for seeking ways to improve that care. The “irony” is in this information age, nurses are constantly challenged to offer creative approaches to old and new health problems, and to design new and innovative programs. This is an era in which the challenges can best be met by integrating knowledge about biological, behavioral, cultural and environmental influences on health into practice. Evidence-based nursing education offers a framework to support, facilitate, develop and foster a questioning approach to nursing. Evidence-based nursing education is using the best available empirical evidence in making decisions about education in nursing. Through education using the most current evidence, current policies and up-to-date procedures, standards in practice are developed and maintained by health professionals. It is fundamental that evidence is to be used taking consideration in clinical judgment and acknowledgement of values, concerns and preferences of individual patient. Therefore it is essential for nurses to be able to evaluate the strength of the evidence and critique practice pattern so they can determine how appropriate the nursing care is.